1993
DOI: 10.1161/01.res.72.6.1293
|View full text |Cite
|
Sign up to set email alerts
|

Delayed effects of sublethal ischemia on the acquisition of tolerance to ischemia.

Abstract: The infarct-limiting effect of ischemic preconditioning is believed to be a transient phenomenon. We examined the delayed effects of repetitive brief ischemia on limiting infarct size in an open-chest dog model by an occlusion (90 minutes) of the left anterior descending coronary artery (LAD) followed by reperfusion (5 hours). The dogs were preconditioned with four brief repeated ischemic episodes induced by 5-minute LAD occlusions with subsequent reperfusion. The size of infarcts initiated by a sustained occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
284
0
18

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(314 citation statements)
references
References 23 publications
9
284
0
18
Order By: Relevance
“…After the initial description of PC in 1986 [1], the next major discovery was in 1993, when it was found that this phenomenon is not monolithic but rather consist of two chronologically and pathophysiologically distinct phases: an early phase, which develops very quickly (within few minutes from the exposure to the stimulus) but is rather ephemeral, lasting only 1-2 h (this is the phenomenon originally described by Murry et al [1]), and a late phase, which develops more slowly (requiring 6-12 h) but lasts much longer (3-4 days) [6,7]. The mechanism for these two phases is completely different.…”
Section: Introductionmentioning
confidence: 85%
“…After the initial description of PC in 1986 [1], the next major discovery was in 1993, when it was found that this phenomenon is not monolithic but rather consist of two chronologically and pathophysiologically distinct phases: an early phase, which develops very quickly (within few minutes from the exposure to the stimulus) but is rather ephemeral, lasting only 1-2 h (this is the phenomenon originally described by Murry et al [1]), and a late phase, which develops more slowly (requiring 6-12 h) but lasts much longer (3-4 days) [6,7]. The mechanism for these two phases is completely different.…”
Section: Introductionmentioning
confidence: 85%
“…In 1993, Kuzuya et al [21] reported a late phase of myocardial protection, less intense but more prolonged that lasted 72 hours. The authors attributed this effect to increasing of antioxidant enzymes such as MnSOD.…”
Section: Discussionmentioning
confidence: 99%
“…An early phase of protection that develops within minutes after the preconditioning stimulus lasts for 2-3 h, whereas a late phase of protection that occurs 12-24 h later lasts for 3-4 days (8,21,23). A number of chemical signals that trigger the development of the late phase of preconditioning, including adenosine, NO, reactive oxygen species, and opioid receptor agonists, have been identified (8,23).…”
mentioning
confidence: 99%
“…Activation of protein kinase C (4), protein tyrosine kinases (16), and mitogen-activated protein kinases (33) by these triggers leads to increased expression of the mediators of the late phase of preconditioning. Myocardial protein synthesis of several mediators (or effectors), including inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), aldose reductase, antioxidant enzymes, and heat shock proteins (HSPs), and activation of ATP-sensitive K ϩ (K ATP ) channels play a critical role in late-phase preconditioning (8,15,21,23,24,29). It has been proposed that activator protein 1 (AP-1) and nuclear factor-B (NF-B) may mediate the transcriptional activation of iNOS, COX-2, aldose reductase, and other genes (22,36).…”
mentioning
confidence: 99%